Awareness of using Radiology in Diagnosing COVID-19 among Radiological Students - Alahmadi, Adnan A.S.; Abdeen, Rawan H. (Journal of Education and e-Learning Research, 2020)
The coronavirus (COVID-2019) has spread very rapidly over many countries around the world, producing an outbreak of acute infectious pneumonia. Medical imaging devices play a vital role in early diagnosis, evaluating severity and disease prognosis of confirmed patients with COVID-19. The aim of the study is to evaluate the awareness level of radiology students about COVID-19 and their understanding of the role of radiology devices in diagnosing COVID-19. An online cross-sectional questionnaire was conducted. Seventy-one students participated in this study. This study showed that students were properly aware of the basic knowledge of the COVID-19, 87 % of the students believed that radiology had an important role in diagnosing COVID-19. In addition, 50% of the students believed that CT was the most important modality in diagnosing COVID-19 and 32.35% believed that x-ray was the most important one. Lack of knowledge was found regarding the biomarkers that appear in radiological images in patients with COVID-19. 66.18 % of the students acquired the knowledge from their study in the radiology field and from social media (Twitter). The level of awareness among radiology students is high. There were two main reasons for this high level of awareness: gained education and social media, especially Twitter. The outbreak of the COVID-19 was not only about its health effects but also how the population persevered this pandemic. However, this level of awareness tended to be lower when discussing detailed findings of radiological images such as detailed biomarkers.